1939
DOI: 10.1084/jem.70.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Rôle of Inborn Resistance Factors in Mouse Populations Infected With Bacillus Enteritidis

Abstract: 1. Under conditions in which mouse typhoid is allowed to spread naturally among herds of mice comprised of different proportions of individuals of innately high or low susceptibility: (a) 85 to 95 per cent of the innately susceptible succumb to mouse typhoid in contrast to less than 5 per cent of the innately resistant, regardless of whether either constitutes 25, 50, or 75 per cent of the population respectively. (b) The surviving population is therefore comprised largely of individuals known at the outset to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1940
1940
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…S1 ). Dubos did not cite any of these compelling studies, including the seminal mouse studies published by his colleague at Rockefeller University, Leslie T. Webster, in the Journal of Experimental Medicine , of which he was a prominent editor ( 31 37 ), and rabbit studies conducted by Max B. Lurie on Dubos’ preferred infection for study, tuberculosis ( 38 ). Dubos had brilliantly reviewed the history and challenges of tuberculosis in “The white plague”, which he published in 1952 ( 5 ).…”
Section: A Few Thoughts About Host Genetics and Immunitymentioning
confidence: 99%
“…S1 ). Dubos did not cite any of these compelling studies, including the seminal mouse studies published by his colleague at Rockefeller University, Leslie T. Webster, in the Journal of Experimental Medicine , of which he was a prominent editor ( 31 37 ), and rabbit studies conducted by Max B. Lurie on Dubos’ preferred infection for study, tuberculosis ( 38 ). Dubos had brilliantly reviewed the history and challenges of tuberculosis in “The white plague”, which he published in 1952 ( 5 ).…”
Section: A Few Thoughts About Host Genetics and Immunitymentioning
confidence: 99%
“…No. In (4) was never able to demonstrate the reality of the "small immunizing dose " (For an opposite view see Greenwood et al,2. ) Webster turned to the hypothesis that the variation in the disease response was due to variation among the mice.…”
Section: The Genetic Basis Of Nutrition Effects In Natural Resistancementioning
confidence: 99%
“…The results from different routes of injection may be compared, but never directly. 4. In deficiency experiments, basal rations.…”
mentioning
confidence: 99%
“…Webster showed that identical doses, directly administered, produced the same diversity in disease effects (3). Is it because some mice first encountered, by chance, a "small immunizing dose" and thus were able to survive the subsequent, larger (4) was never able to demonstrate the reality of the "small immunizing dose " (For an opposite view see Greenwood et al,2. ) Webster turned to the hypothesis that the variation in the disease response was due to variation among the mice.…”
Section: The Genetic Basis Of Nutrition Effects In Natural Resistancementioning
confidence: 99%